Um framework de competências digitais para professores a partir de análises de matrizes internacionais - Bastos, Thais Basem Mendes Correa (2020)
The current educational scenario, regarding the use of digital technologies, requires teachers to have specific knowledge and skills in the teaching and learning process, and it is necessary to rethink pedagogical and teacher training strategies. This research project presents a reflection on digital competences for teachers from international policies, more specifically, from countries that are members of the Organization for Economic Co-operation and Development (OECD), contextualizing it those with the Brazilian reality. Initially, a systematic literature review was developed on the concept of competence, in order to reinforce its complexity when applied to teachers. Then, through a reconstructive analysis of documents from Germany, Australia and South Africa, a matrix of digital skills for teachers was drawn up, in line with the Brazilian National Educational Plan, the Common National Curricular Base and the National Curriculum Guidelines and Base National Program for Initial and Continuing Education of Basic Education Teachers and, based on this matrix, a digital skills framework for teachers with targeted language was developed.